Exploring the role of L2 in L1 writing clues from English teachers' think aloud protocols - Torres, Joel M.; Flores, Eden Regala (2017)
In the past, the ESL/EFL field has intensively exposed the effects of L1 to L2, yet overlooked the possible effects of L2 to L1. Hence, this study is an attempt to offer an initial answer as regards the considerable interest in how bilinguals make use of their language repertoires when engaged in an L1 composing task. Four Filipino English teachers from four senior high schools were asked to compose essays in their L1(Tagalog). Think Aloud Method was used to identify the roles of L2 (English) during the L1 composing activities and a semi-structured interview was carried out to determine participants' reason for language switching. data from their Think-Aloud Protocols revealed that L2 was adopted as a common strategy during the L1 composing process particularly in text-generating (producing and reviewing the text), idea-generating (planning), idea-organization (planning), task explaining, and process-controlling. The amount of L2 used varied with each category of composing activities and among the participants. Participants' exposure to L2 and the lack of equivalent concepts in L1 made the participants resort to their L2 while writing in their L1.
Keywords: Linguistic; Writing